"Problem Free is Not Fully Prepared": Exploring the Difference Between Prevention and Promotion Oriented Educational Indicators as Related to U.S. State Demographic Characteristics. (July 2021) - Ilakkuvan, Vinu; Price, Olga A.
This study assessed whether U.S. state-level prevention- and promotion-oriented indicators of student success are differentially associated with state-level demographic characteristics. Correlation and regression analyses were used to assess the relationship between state-level demographics and promotion-oriented (school engagement, extracurricular involvement, and feeling safe at school) and prevention-oriented indicators (high school dropout and grade 4 chronic absenteeism). State demographic factors were more strongly correlated with—and more predictive of—involvement in extracurricular activities and feeling safe at school, as compared to school engagement or the prevention-oriented indicators. That is, promotion-oriented indicators appear to be substantively different than prevention-oriented indicators in terms of their relationship to state socioeconomic and racial/ethnic characteristics. This suggests current overreliance on prevention-oriented indicators may fail to fully capture student well-being and differential access to effective policies and supports between states. States should include promotion-oriented measures in their educational assessments, reporting, and accountability systems to more comprehensively understand student success and what can be done to improve student well-being and related socioeconomic conditions—particularly through state-level policies and school‐community partnerships.